Freshwater gastropods in the Northern littoral mesoregion of Espírito Santo, Brazil (Acta Scientiarum. Biological Sciences, 2017)
Studies on the distribution of molluscs in Brazilhave been conducted since the beginning of the twentieth and the knowledge of the species distributed in the country represent important findings, which contribute to the understanding of human diseases and those of veterinary importance, transmitted by them. In order to verify the distribution of freshwater gastropods in Espírito Santo, a malacological surveywas carried out in nine municipalities that comprise the Northern mesoregion of the State, between January 2010 and February 2015. Initially the water collections occurring in the municipality were verified and the lotic systems at different levels of use and conservation were determined. Molluscs were collected monthly using a hand net adapted to a stick steel. An individual sample effort of 30 minutes was applied, by scanning, at about ten meters in each one of the selected habitats. A total of 6,000 specimens were collected, represented by genera Melanoides, Drepanotrema, Physa, Biomphalaria and Pomacea. Among the molluscs, some specimens were positive for flatworm larvae of medical and veterinary importance. The results contributed to the knowledge of the current distribution of freshwater gastropods in the Northern region of Espírito Santo whose the only record for the region dates back to 1983.